2019
DOI: 10.21511/bbs.14(3).2019.07
|View full text |Cite
|
Sign up to set email alerts
|

Taxation, exchange rate and foreign direct investment in Nigeria

Abstract: This paper investigates factors that may impact foreign direct investment in Nigeria. It seeks to establish the role of taxation (corporate tax) for foreign direct investment in Nigeria. Annual time series data derived from the Central Bank of Nigeria statistical bulletin and the United Nations Conference on Trade and Development covering a period of 31 years (1985–2015) were used for this study. The variables considered in the study include FDI, corporate tax, exchange rate, inflation rate, real gross domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…The estimated results also show that the coefficients of GDPGR and INTR, shows a positive sign and insignificant statistically (Abu & Abdullah, 2010). The positive coefficient of the growth rate of the GDP and CPI conforms to the findings of Uwuigbe et al (2019) on the relationship between corporate taxation and FDI in Nigeria that GDP was positively insignificantly relationship with FDI while inflation had positive significant relationship with FDI.…”
Section: Thesupporting
confidence: 84%
“…The estimated results also show that the coefficients of GDPGR and INTR, shows a positive sign and insignificant statistically (Abu & Abdullah, 2010). The positive coefficient of the growth rate of the GDP and CPI conforms to the findings of Uwuigbe et al (2019) on the relationship between corporate taxation and FDI in Nigeria that GDP was positively insignificantly relationship with FDI while inflation had positive significant relationship with FDI.…”
Section: Thesupporting
confidence: 84%
“…In a related study, Ojeka et al (2021) investigated the effect of the tax rate on the inflow of foreign direct investment to the Sub-Saharan African countries and failed to provide empirical evidence in support of a significant relationship between tax rate and inflow of foreign direct investment, though it showed a positive relationship. Uwuigbe et al (2019) studied the role of taxation and exchange rate on the inflow of foreign direct investment in Nigeria for the period of 1985 t0 2015. The study employed the Ordinary Least Square method of estimation and found that the corporate tax rate has a negative and significant effect on the inflow of foreign direct investment in Nigeria for the period under investigation.…”
Section: Literature Reviewmentioning
confidence: 99%